Nanoparticles surface treatment on cemented materials for inhibition of bacterial growth. (30th September 2017) - Noeiaghaei, Tahereh; Dhami, Navdeep; Mukherjee, Abhijit
Highlights: Bactericidal characteristics of cementitious materials treated with nanoparticles is reported. Untreated zinc oxide and PVP-capped silver nanoparticles have been compared. A range of surface pH of mortar samples and bacterial cell densities have been investigated. After the seven-day period, more than 60% reduction of viable cells was observed. Stabilisation of nanoparticles reduced aggregation and favoured a consistent long-term performance. Abstract: Bacterial growth on cemented materials such as concrete can cause degradation and early ageing. This paper explores the bactericidal characteristics of cementitious materials surface treated with zinc oxide (ZnO) and silver (Ag) nanoparticles. The growth of gram positive Bacillus cereus and gram negative Escherichia coli has been monitored. The growth inhibitory performance of nanoparticles against two model bacteria was further examined at different surface pH of mortar samples and different bacterial cell densities. After the seven-day experimental period, more than 60% reduction in the number of viable cells of both model bacteria was obtained at all tested pH values when nanoparticles with a concentration of 250 mg/l were added at the beginning of culturing time. However, delayed addition of nanoparticles at the mid-logarithmic growth phase, i.e., higher cell densities, resulted in less growth inhibition. Ag nanoparticles showed the highest inhibition due to the high degree of nanoparticle stability and uniform particle size. On the other hand, the stability of ZnO nanoparticles in the experimental mixture was significantly influenced by the pH change and aggregation, which resulted in lower inhibition efficiencies. Gram-positive Bacillus cereus was found to be less sensitive to both tested nanoparticles, compared with Gram-negative Escherichia coli. The experiment demonstrates the efficacy of nanoparticles in inhibiting bacterial growth on cementitious materials.